The Influence of Work Culture on Work performance of Employees in Department of Transportation, Communication and Informatics of West Sumatera - Aldri Frinaldi (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2017)
AbstractThe goals of bureaucratic reform were to increase the service quality provided for society and stakeholders and to enhance the work performance in order to be able to carry out their duties and functions. Bureaucratic reform needs alteration of work culture which is not only addressed to the employees but also to the functionary as the leader in government or local government. The problem in this research was whether there was influence of work culture among civil servant on work performance in Department of Transportation, Communication and Informatics of West Sumatera Province or not. This research was a quantitative research and consisted of work culture as the independent variable and work performance as the dependent variable. The number of the sample was 87 apparatus. The data were taken by using a questionnaire with Likert scale and were analyzed by using study documentation and simple regression technique. The research found that; (1) The influence of work culture on justice was 0,265; (2) The influence of work culture on decency and fairness was 0,048; (3) The influence of work culture on work quantity was 0,189; (4) The influence of work culture on discipline was 0,460; and (5) The influence of work culture on work performance as a whole was 0,285. The conclusion was work culture of the employees of Department of Transportation, Communication and Informatics of West Sumatera Province positively influenced work performance as a whole and also influenced each indicator of work performance significantly. Department of Transportation, Communications and Information Technology of West Sumatera province have to pay attention to the work culture in its office to enhance the performance of the employee by improving the positive work culture, encouraging the noble value in workplace and improving work performance indicators other than discipline, namely justice, decency and fairness, and quantity of work. Keywords: Work culture, Work Performance, Government Employees.